Impact of the U.S.–China trade war on the operating performance of U.S. firms: The role of outsourcing and supply base complexity - Fan, Di; Zhou, Yi; Yeung, Andy C. L.; Lo, Chris K. Y.; Tang, Christopher (Journal of Operations Management, 2022)
AbstractMultinational corporations have benefited tremendously from free trade in the past few decades. However, the dynamism of international relations, paired with the global recession, has rekindled the debate over frictionless trade. In this study, we examine how trade friction, created by tariff trade barriers, affects the operational performance of domestic firms which source from the affected countries. We also investigate how various supply chain characteristics and strategies can moderate the impact of such trade friction. Motivated by the 2018 U.S.–China trade war, we conducted a difference‐in‐difference analysis to examine the impact of trade tariffs on performance indicators of U.S. firms with direct supplier connections in China. Specifically, we found that U.S. firms with direct supply partners (i.e., first‐tier suppliers) in China had a worse performance than the U.S. firms without direct supply partners in China in terms of inventory (i.e., days of supply) and profitability (return‐on‐assets). We further found that the negative impacts were more severe for firms with a higher degree of outsourcing, and horizontal and spatial supply base complexity. We discuss the implications for international operations management, supply chain networks, supply risk management, and provide suggestions to supply chain practitioners and trade policymakers.